Impact of strategic orientation adopted by an organisation on its performance, as shown on the example of public healthcare entities = Wpływ orientacji strategicznej organizacji na efektywność jej funkcjonowania na przykładzie publicznych podmiotów leczniczych - Szymaniec, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The resource-based view has an established position in the strategic management of a public organisation. However, it is not given much attention in the area of public governance, focusing instead on analysing the impact of a single resource on an organisation?s performance. This article attempts to fill this gap by analysing the impact of strategic orientation adopted by an organisation on its performance.
Keywords: podejście zasobowe; zarządzanie publiczne; organizacja publiczna; interesariusze; publiczny podmiot leczniczy; resource-based view; public governance; public organisation; stakeholders; public healthcare entity